POTENSI PEMANFAATAN HASIL HUTAN BUKAN KAYU POHON AREN DI KELURAHAN KAYAWU KOTA TOMOHON - Cindy Eva Saragih; Marthen Theo Lasut; Euis F. S. Pangemanan (Universitas Sam Ratulangi, 2020)
ABSTRACT POTENTIAL UTILIZATION OF NON-AREN FOREST PRODUCTS IN KAYAWU VILLAGE, TOMOHON CITY Sugar palm is one of the HHBK that is widely used, one of which is palm sugar, or also known as